Markedly elevated blood pressure, tachycardia, and altered consciousness in patients with bacteremia during transurethral surgeries: two case reports - Arisa Hotta; Momoka Nishimura; Daisuke Nakada; Riko Uchida; Hiroshi Matsuura; Naoko Torii; Naoko Fujita; Taku Hamada; Ai Nakamoto; Noriko Yoshikawa (JA Clinical Reports)
Abstract Background Transurethral surgery is often accompanied by postoperative urinary tract infection. Although early detection and adequate treatment of bacteremia are required to prevent sepsis, it is usually undetectable during surgery. We report two cases with remarkable hypertension and tachycardia during transurethral surgery in which bacteremia was diagnosed by an intraoperative blood test. Case presentation An 80-year-old man (Case 1) underwent transurethral holmium laser prostate enucleation under spinal anesthesia, and an 88-year-old woman (Case 2) underwent transurethral resection of bladder tumor under general anesthesia. Altered consciousness (Case 1) and postoperative delirium (Case 2) were noted, in addition to remarkable intraoperative hypertension and tachycardia. We administered broad-spectrum antibiotics for possible bacteremia in both cases. The patients’ hemodynamics positively recovered the following day. Intraoperative blood samples revealed gram-negative bacillus. Conclusions Hypertension, tachycardia, and altered consciousness may suggest the onset of symptomatic bacteremia during transurethral surgery, and adequate treatment is required to prevent sepsis.